Media Pembelajaran Fisika dengan Adobe Flash Pro CS6 pada Materi Getaran Harmonik Sederhana - Ita Laila; Hairunnisyah Sahidu; Gunawan Gunawan (Indonesian Journal of Applied Science and Technology, 2020)
The development of the 21st century is marked by the use of information and communication technology in all aspects of life, including in the learning process. The learning process at SMA Negeri 7 Mataram experienced problems related to the not optimal use of learning media, especially in learning physics. This development research aims to: (1) find out how to develop learning media with Adobe Flash Pro CS6 on simple harmonic vibration material. (2) determine the feasibility of learning media with Adobe Flash Pro CS6 on simple harmonic vibration material. This research is development research (R&D) with the model used as 4D Models (define, design, develop, and disseminate). The process of assessing learning media feasibility was carried out by giving questionnaires to five material expert validators and media experts. The study results were learning media products for simple harmonic vibration material with Adobe Flash Pro CS6 with the results of the assessment of six material expert validators getting an average score of 3.34 in the very feasible category. The assessment results of the six media expert validators got an average score of 3.50 in the very feasible category. Based on these data, it can be concluded that the learning media using Adobe Flash Pro CS6 for simple harmonic vibration material are declared suitable for use in learning.